The Effect of Honey Supplementation on Skeletal Muscle‐Related Inflammatory Markers Among Military Graduates After Overtraining - Esmail Karami; Mohammad Reza Parvizi; Mohammad Reza Izadi; Emad Jowhari Shirazi (Health Science Reports)
ABSTRACT Aims and Objectives Honey possesses specific anti‐inflammatory properties. We evaluated the effects of oral honey supplementation on skeletal muscle‐related inflammatory markers among military graduates after overtraining. Methods This randomized double‐blind controlled trial was conducted on 42 overtrained military graduates who were randomly assigned to receive either honey supplementation (5 mL of 12% honey solution twice daily for 6 weeks) or a placebo for 6 weeks. In our study, we utilized Milk Vetch Sahand honey as the intervention. Serum levels of C‐reactive protein (CRP), tumor necrosis factor‐α (TNF‐α), aldolase A, and creatine kinase (CK) were evaluated using the enzyme‐linked immunosorbent assay method before and after the intervention. Results A total of 21 male participants with a mean age of 20.75 years were included in each group. No significant differences were found between the groups in the pre‐intervention assessment of inflammatory biomarkers. However, in the post‐intervention assessment, participants who received honey exhibited significantly smaller increases in CRP (p < 0.001), TNF‐α (p = 0.001), aldolase A (p < 0.001), and CK levels (p < 0.001) compared to the controls. The mean changes in these biomarkers were notably lower in the honey group indicating a potential anti‐inflammatory effect of honey. Conclusion This study demonstrates that honey supplementation significantly reduces inflammatory biomarkers such as TNF‐α, CRP, aldolase A, and CK in military graduates experiencing overtraining, underscoring its potential to alleviate inflammation associated with intense physical training. To confirm and extend these findings, further research with larger sample sizes and longer follow‐up periods is recommended.